2004
DOI: 10.1111/j.0029-6473.2004.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Concept Mapping: An Educational Strategy for Advancing Nursing Education

Abstract: Instructors and students reported satisfaction from use of concept maps in the educational process. Teaching with the aid of concept maps has been incorporated as an innovative and viable teaching method in nursing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 8 publications
6
24
0
1
Order By: Relevance
“…According to Pinto and Zeitz (1997), concept maps can facilitate students' understanding of the organization and integration of important concepts. By connecting old and new knowledge, this type of learning clarifies knowledge, improves critical thinking and assists in completing missing knowledge (Harpaz, Balik, & Ehrenfeld, 2004).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…According to Pinto and Zeitz (1997), concept maps can facilitate students' understanding of the organization and integration of important concepts. By connecting old and new knowledge, this type of learning clarifies knowledge, improves critical thinking and assists in completing missing knowledge (Harpaz, Balik, & Ehrenfeld, 2004).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…For example, Harpaz, Balik, and Ehrenfeld (2004) recently demonstrated the efficacy of concept mapping in encouraging students to think independently and to find connections among concepts. Concept maps are powerful tools for helping learners identify general concepts prior to instruction focused on more specific content, as well as an evaluation tool of the knowledge that is formed afterward (Mintzes, Wandersee, & Novak, 2000;Novak and Gowin, 1984).…”
Section: Concept Mapping As a Tool For Learningmentioning
confidence: 99%
“…Second, nursing education scholars were evaluating and assessing the ways in which concept maps functioned as a learning strategy (Abel & Freeze, 2006;August-Brady, 2005;Banning, 2006;Bowles, 2006;Brunt, 2005;Chabeli, 2010;Clayton, 2006;Ellermann, Kataoka-Yahior, & Wong, 2006;Fonteyn, 2007;Garrett, 2005;Gul & Bowman, 2006;Harpaz, Balik, & Ehrenfeld, 2004;Hay, 2007;Hicks-Moore, 2005;Hicks-Moore & Pastirik, 2006;Hill, 2006;Hsu, 2004;Hsu & Hsieh, 2005;Johns, 2003;Kinchin & Hay, 2005;King & Shell, 2002;Laight, 2006;Latini, 2009;Luckowski, 2003;Pardue, Tagliaren, Valiga, Davison-Price, & Orehowsky, 2005;Pilcher, 2009;Senita, 2008;Staib, 2003;Vacek, 2009;Veo, 2010;Walsh & Seldomridge, 2006;Wheeler & Collins, 2003). This body of work looked at concept maps as a strategy to promote meaningful learning, a method for collaborative learning, a strategy to promote higher level thinking, critical thinking and clinical decision making, and a methodology for fostering the linkages between theory and practice in a clinical setting.…”
Section: Expansion and Adaptation (2000-2010)mentioning
confidence: 99%
“…Several authors (Harpaz et al, 2004;Luckowski, 2003;Schuster, 2000) reported on the positive learning outcomes of their work with concept maps, and yet the examples shared in published manuscripts did not use linking words between concepts, nor were there horizontal connections (i.e., integrative reconciliation) between concepts. It appeared that this adaptation came from a misunderstanding of Novak's and Gowin's (1984) original work on concept maps and the theoretical framework of assimilation theory of learning (Ausubel, 2000) that supports proper concept map development.…”
Section: Adaptation (2000-2010)mentioning
confidence: 99%